Analysis of the need for science literacy-based textbooks to improve students' competence in the earth and space course - Puardmi Damayanti; Shelly Efwinda; Abdul Hakim; Muliati Syam; Putri Dwi Sundari (Journal of Environment and Sustainability Education, 2025)
In the 21st-century learning era, the quality of teaching materials is crucial in meeting current educational needs. This study highlights the urgency of developing a science literacy-based textbook for the Earth and Space course to enhance students' scientific literacy competence in the Physics Education Study Program at Mulawarman University. The research aims to analyze the necessity of such a textbook using the 4D development model, focusing on the Define phase to identify key learning challenges and curriculum needs. Data were collected through classroom observations, student questionnaires involving 42 participants from the 2023 cohort, and the formulation of learning outcomes aligned with the three scientific literacy competencies of the Programme for International Student Assessment (PISA): (1) explaining scientific phenomena (2) evaluating and designing scientific investigations, and (3) interpreting data and scientific evidence. The data analysis process involved data reduction, presentation, and conclusion drawing. The findings indicate that the current teaching materials do not fully support the learning objectives, leading students to rely on fragmented online resources, often in English. The study also identified a strong demand for structured, interactive textbooks integrating scientific literacy. The validation process involved three expert validators using a Likert scale assessment. This validation resulted in eight valid learning outcomes (CPMK) with a corrected item-total correlation of r > 0.3 and a Cronbach's Alpha of 0.848, confirming high reliability. These findings provide a foundational framework for developing an Earth and Space textbook, ensuring its alignment with science literacy competencies in subsequent research phases.